Peran Peserta Didik Sebagai Agen Perubahan Dalam Mencegah Perundungan (Bullying) Di SMA Negeri 1 Panyabungan - Ali Jusri Pohan; Rindy Regar; Ami Rizkiana; Rizky Khofifah; Fitri Yanti Lubis; Muhammad Alwi Nasution; Rezky Pramana Putra (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
Bullying has long been a phenomenon haunting educational environments worldwide, with its impacts not only affecting the victims individually but also influencing the overall image of the school. Bullying can lead to a decline in academic achievement, loss of students' self-confidence, and even mental health disorders among victims. Additionally, bullies themselves may experience negative consequences, such as difficulty in forming healthy social relationships with others in the future. In recent years, awareness of the importance of addressing bullying has significantly increased. Schools, parents, and communities are becoming more aware of the actions needed to prevent and address bullying cases in schools. One approach that has been implemented is through the introduction of programs like the Roots Program. The Roots program is designed to promote values such as respect for others, openness, freedom of expression, trust, and safety within the school environment. By involving the entire school community, including students, teachers, staff, and parents, this program aims to create a positive school climate where bullying can be effectively addressed.This research aims to implement the Roots program with the involvement of change agents, with the hope of providing deeper insights into the effectiveness of this program in combating bullying in schools. A qualitative approach focusing on phenomenology is employed in this study. The research location is SMA Negeri 1 Panyabungan, North Sumatra. Data are obtained from primary sources consisting of research subjects, including the school principal, teachers, and members of the Change Agents. Subject selection for the research uses purposive sampling technique. The Bullying Prevention Program, based on Ministry of Education and Culture Regulation No. 82 of 2015, aims to create a safe and comfortable school climate for students. Change Agents at SMA Negeri 1 Panyabungan play a crucial role in implementing this program by positively impacting students and the school as a whole. The success of this program is measured through the ability of change agents to prevent and address bullying incidents in school, as well as through the celebration of the Roots Day Declaration involving the entire school community. It is hoped that this program will help reduce bullying cases and create a more friendly and enjoyable school environment for all involved parties.